A way of relating to life; myself and others - a thematic analysis of patients’ experience of having an eating disorder - Malin Bäck; Sanna Aila Gustafsson; Karin Jacobson; Theresia Ljung; Rolf Holmqvist; Gerhard Andersson (Journal of Eating Disorders)
Abstract Background Eating disorders are psychiatric conditions that extend beyond concerns with weight, body and shape, encompassing complex issues related to self-esteem, emotion regulation and interpersonal functioning. Moreover, co-occurring depression, often undiagnosed, is a common complicating factor. Gaining an in-depth understanding of living with an eating disorder is vital both theoretically and for identifying factors that maintain or inhibit recovery. Patient-centred studies offer valuable insights into the lived experience of eating disorders, highlighting their impact and interaction with various life phenomena. Methods This qualitative study aimed to capture the meaning and experience of living with an eating disorder from a patient perspective. Semi-structured interviews were conducted with 15 women suffering from eating disorders and comorbid depressive symptoms, prior to the start of treatment. Data were analysed using reflexive thematic analysis. Results Two dimensions of relating to the eating disorder emerged. The first dimension, “Relating to the eating disorder over time”, followed a temporal trajectory with four themes: “The eating disorder as a way to handle other difficulties”, “From control to a consistent loss of control”, “The whole existence revolves around the eating disorder” and “Hard to see a life without the eating disorder”. The second dimension, “Having an eating disorder– a relentless relating”, focused on the present experience and was divided into two themes: “The eating disorder’s impact on relating to myself” and “The eating disorder’s impact on relating to others”. Conclusions Living with an eating disorder involves a constant, entangled and conflicted relationship with the disorder, leading to alienation from significant others and one’s own body. This pervasive presence of disordered thoughts and behaviours makes it challenging to relate to oneself and the external world without their influence. Over time, the disorder becomes increasingly ego-syntonic, rendering it difficult to envisage a life without it. Treatment should, therefore, aim to externalise the disorder—to foster new life goals, enhance social engagement, and improve interpersonal skills. Further research is needed to elucidate how co-occurring depressive symptomatology influences an individual’s relationship with their eating disorder, as these factors may be crucial in tailoring effective interventions.